Dinamika Akuntabilitas Badan Pengawasan Keuangan Dan Pembangunan Provinsi Bali Dalam Perspektif Good Governace - Tu Adi, I Wayan; Sri Rahayu Gorda, AAA. Ngurah (Politeknik Negeri Jember, 2024)
ABSTRACT This Field Work Practice report raises the theme of the dynamics of accountability of the Bali Provincial Financial and Development Supervisory Agency within the framework of Good Governance. With an emphasis on the importance of transparency and accountability in financial and development supervision, this research explores the underlying background, formulates the problems faced, sets the objectives and benefits of the report, and presents the results of the reporting work along with in-depth analysis. Through a comprehensive review, it was found that Supervisory Bodies have a crucial role to play in ensuring accountability and transparency in financial and development oversight. In conclusion, stronger synergies between agencies and improved evaluation mechanisms are needed to enhance good governance. Suggestions include increasing public participation, upholding the rule of law, and improving the effectiveness and efficiency of financial and development oversight institutions. Keywords — Accountability. Good Governance, Supervision